THE STUDENTS' ABILITY IN WRITING DESCRIPTIVE TEXT AT SMP NEGERI 7 LUBUKLINGGAU - Roselia Putri Lestari; Maria Ramasari; Dewi Syafitri (Lingustic, Literature and English Education, 2022)
Abstract The problem in this research was “How was the ability of students in writing descriptive text?” and “What were the difficulties faced by students in writing descriptive text?” The objective of this research was to describe the ability of students in writing descriptive text and to describe the difficulties faced by students in writing descriptive text. This research used quantitative method to and data collected in write descriptive text. The population in this research was all the eighth grade students of SMPN 7 Lubuklinggau. The sample of this research was VIII.2 considered 27 students who taken class by using random sampling. Based on the result of the writing descriptive text at the eighth grade students of SMPN 7 Lubuklinggau was in (failed category). The mean score of students was 61. There were 5 students(18%) on Very Good category, 5 students on (18%) Good category, 1 student (4%) on Nearly Good category, 8 students on (30%) Sufficient category, and the last 8 students on (30%) Nearly Sufficient category. It means that the ability of students in writing descriptive text was categorized into Nearly Good, and their ability was categorized into failed (the students’ score were lower than KKM 61< 68). In conclusion, the biggest difficulties faced by students were about grammar, and organizing the ideas. Keywords: Descriptive Text, Difficulties in writing, Students’ Ability